Factors That Reduce The Incidence of Lung Tuberculosis Other Than Isoniazid Preventive Therapy (IPT) in Latent Igra Positive HIV-TB Patients - Aryati; Karina Yuniati, Shinta; Kusmiati, Tutik; Triyono, Erwin Astha (Journal of Diverse Medical Research: Medicosphere, 2024)
Background. One crucial public health measure to stop persons living with HIV (PLWHA) from developing active TB is isoniazid preventative therapy (IPT). Only few hospitals in Indonesia continue to offer IPT. Aim. The purpose of this study was to assess how IPT affected the incidence of TB in patients with latent HIV infection. Method. This study uses a prospective cohort design and is quasi-experimental in design. Samples for the study were obtained by convenience sampling and the study was carried out in the inpatient and outpatient departments of UPIPI Dr. Soetomo Hospital. Latent IGRA positive HIV-TB patients who satisfied the inclusion requirements made up the samples. Result. Of the 59 patients who finished the screening exam, 23 fulfilled the inclusion requirements for this study. Using the ELISPOT method, the IGRA T-SPOT.TB test yields 36 (64.29%) negative findings and 23 (35.18%) positive results. After six months of IPT administration, analysis of the data revealed that the incidence of active pulmonary TB in latent HIV-TB patients was 0% in the IPT group and 0% in the non-IPT group. Antiretroviral medication used for more than four years and a CD4+ T lymphocyte count of more than 200 cells/μL were factors that contributed to the lack of pulmonary tuberculosis in both groups. Conclusion. ARV used for more than four years and CD4+ lymphocyte count more than 200 cells/L contributing significantly in pulmonary tuberculosis incidence.